Merdeka Curriculum implementation at Wonoayu 1 Junior High School as Sekolah Penggerak - Varary Mechwafanitiara Cantika; Lathifah Khaerunnisa; Rika Yustikarini (Universitas Pendidikan Indonesia, 2022)
The concept of Ki Hadjar Dewantara's education was adopted in Indonesia's current curriculum, known as Kurikulum Merdeka. The Kurikulum Merdeka Curriculum is implemented with the support of all stakeholders and policymakers, following the school's readiness. Wonoayu 1 Junior High School is one of the schools that has become “Sekolah Penggerak” and because of its readiness, the school implements Kurikulum Merdeka. This study aims to describe the implementation of the Merdeka curriculum at Wonoayu 1 Junior High School, Sidoarjo Regency, as “Sekolah Penggerak”. The method used in this research is a descriptive method with a qualitative approach. Data collection techniques using interviews and observation. The results showed that implementing Kurikulum Merdeka at Wonoayu 1 Junior High School followed the standards and curriculum guidelines for implementing Kurikulum Merdeka for “Sekolah Penggerak”. These aspects are viewed from three main aspects: the learning planning aspect, the learning implementation aspect, and the learning assessment aspect. Some obstacles require more attention and further handling in implementing Kurikulum Merdeka at Wonoayu 1 Junior High School.